2013
DOI: 10.1016/j.pep.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of active receptor interacting protein 1 kinase using a baculovirus system

Abstract: Receptor Interacting Protein 1 (RIP1) kinase is one of the key mediators of tumor necrosis factor alpha (TNF-α) signaling and is critical for activation of necroptotic cell death. We developed a method for expression of recombinant kinase, utilizing baculovirus co-infection of Cdc37, an Hsp90 co-chaperone, and RIP1-His, followed by a two-step purification scheme. After optimization, 1-3 mg of highly purified RIP1 kinase was typically obtained from a 1 L of Sf9 cells. The recombinant protein displayed kinase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In contrast, ponatinib displayed ~3-fold higher activity in vitro than in cells. We have previously optimized the length of RIPK1’s kinase domain (recombinant RIPK1, a.a. 1–327) to maximize its catalytic activity (Maki and Degterev, 2013; Maki et al, 2013) and, hence, the kinase active Glu-in conformation. The Glu-in conformation creates an additional energy barrier (due to the loss of a highly conserved Glu/Lys ionic bond in the Glu-out conformation) that must be overcome by necrostatins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, ponatinib displayed ~3-fold higher activity in vitro than in cells. We have previously optimized the length of RIPK1’s kinase domain (recombinant RIPK1, a.a. 1–327) to maximize its catalytic activity (Maki and Degterev, 2013; Maki et al, 2013) and, hence, the kinase active Glu-in conformation. The Glu-in conformation creates an additional energy barrier (due to the loss of a highly conserved Glu/Lys ionic bond in the Glu-out conformation) that must be overcome by necrostatins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both RIP1 and RIP3 are clients of the HSP90-CDC37 cochaperone complex. Although it has been previously reported that RIP1 can be better expressed and purified when coexpressed with CDC37, and an HSP90 inhibitor caused the down-regulation of the RIP1 protein level (22,25,26), it is now clear that not only are both latent RIP1 and RIP3 associated with the HSP90-CDC37 complex, their activation during necroptosis is critically dependent on the activity of such a chaperone complex. Interventions with either chemical HSP90 inhibitors or CDC37 knockdown blocked RIP1-RIP3 interaction, RIP3 autophosphorylation, and the ensuing necroptosis.…”
Section: Discussionmentioning
confidence: 99%